2017
DOI: 10.5935/0946-5448.20170010
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus, Anxiety, Depression and Substance Abuse in Rock Musicians a Norwegian Survey

Abstract: Objective: Rock musicians are known to have an increased prevalence of hearing loss and tinnitus. The aims of the present study were to examine the distribution of anxiety and depression symptoms among rock musicians with or without tinnitus and how these mental health indicators and internal locus of control influenced upon their tinnitus symptom concerns and the degree to which the tinnitus affected their lives. Design: The study was a questionnairebased cross-sectional survey of subjects selected from a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In our study, adults with MDD were more than three times more likely to report tinnitus on multivariable analysis. This is consistent with other prospective (23,24) and cross-sectional studies (20,25,26), which suggest a significant correlation between MDD and tinnitus. Although the association between cannabis use and tinnitus was significant on multivariable analyses in this study, the difference in tinnitus prevalence between different levels of cannabis use was no longer statistically significant in the subpopulation of participants with depression.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, adults with MDD were more than three times more likely to report tinnitus on multivariable analysis. This is consistent with other prospective (23,24) and cross-sectional studies (20,25,26), which suggest a significant correlation between MDD and tinnitus. Although the association between cannabis use and tinnitus was significant on multivariable analyses in this study, the difference in tinnitus prevalence between different levels of cannabis use was no longer statistically significant in the subpopulation of participants with depression.…”
Section: Discussionsupporting
confidence: 93%
“…Findings amongst nonmusicians have suggested weak to moderate association between tinnitus and stress [64,65] and some evidence has suggested a bidirectional relationship between stress and selfreported hearing problems including tinnitus [66]. Furthermore, musicians experiencing tinnitus have reported experiencing more depressive symptoms than non-musicians with tinnitus [51]. Some musicians in the present study attributed their mental health problems to their experience of tinnitus and highlighted that "mental health support is key" (PM12).…”
Section: Support Pms Receive or Need Because Of Tinnitusmentioning
confidence: 66%
“…As previous research reported, musicians are at risk of noise exposure at work [14][15][16][17][18], and they may be aware that their tinnitus has arisen from occupational noise exposure leading to some feelings of personal responsibility and control. An internal locus of control has been suggested to be a mediating factor in how concerned musicians are about their tinnitus [51] and as such may be connected to anxiety experienced.…”
Section: Impact Of Tinnitus On Professional Musicians In the Ukmentioning
confidence: 99%
“…Sleep disturbances are prevalent among individuals with tinnitus, as silence can often accentuate tinnitus symptoms at bedtime. To mitigate tinnitus during nighttime, experts recommend employing white noise or other soothing sounds to mask the tinnitus sound, elevating the pillow to alleviate congestion, and establishing a consistent bedtime routine that incorporates stress-reducing activities [ 36 ]. Reducing the consumption of caffeine, alcohol, and tobacco is imperative for managing tinnitus symptoms, as these substances can exacerbate tinnitus.…”
Section: Reviewmentioning
confidence: 99%